If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + -4 + 1x = 5(9 + -4x) Reorder the terms: -4 + 1x + 1x = 5(9 + -4x) Combine like terms: 1x + 1x = 2x -4 + 2x = 5(9 + -4x) -4 + 2x = (9 * 5 + -4x * 5) -4 + 2x = (45 + -20x) Solving -4 + 2x = 45 + -20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20x' to each side of the equation. -4 + 2x + 20x = 45 + -20x + 20x Combine like terms: 2x + 20x = 22x -4 + 22x = 45 + -20x + 20x Combine like terms: -20x + 20x = 0 -4 + 22x = 45 + 0 -4 + 22x = 45 Add '4' to each side of the equation. -4 + 4 + 22x = 45 + 4 Combine like terms: -4 + 4 = 0 0 + 22x = 45 + 4 22x = 45 + 4 Combine like terms: 45 + 4 = 49 22x = 49 Divide each side by '22'. x = 2.227272727 Simplifying x = 2.227272727
| 2-8x+1(x-4)=2(x-7) | | 6x+3=2x+31 | | m-14.6=9.74 | | 4+2x=5x-2 | | w-8=32 | | 4y-8=5y-1 | | 17dl=l | | 3x+4=-36-5x | | x=2*8+77 | | 16+5x= | | 3x+4=-35-5x | | (2x+5)x(7x-2)=(4x+3)x(5x-1)+82 | | 4(d-7)=524 | | X-4X+3Y+9Y-12=0 | | 5x+3x+120=360 | | 6*x*y-12=0 | | x+3x-4= | | f(x)=2x^4-3x | | y-1=-6/7(14) | | 3(2x+3)=45 | | (2x+5)=27 | | (x-5)10+(1-2x)15=(3-x)14 | | x-12y=-36 | | 80-6x=7x+16 | | 7(9)+9y=63 | | 3y-5x=0 | | 3y+2(-3)=-6 | | (8x-8)/7-4(x+4)/7+7=8 | | x^2-24x-51=0 | | x^3-24x^2-51x=0 | | 15x+12y=13 | | 3x+33=11x-66 |